A materialidade do serviço social frente à investida pós-moderna: uma análise a partir da produção do conhecimento - Duarte, Hadassa Nyedja Elias (2019)
The present Master's Dissertation Academic is entitled THE MATERIALITY OF THE SOCIAL SERVICE FRONT OF POST-MODERN INVESTIGATION: an analysis based on the production of knowledge. It presents as object of study the critical materiality of Social Service in the face of its crisis in the milestones of postmodernity. It aims to analyze historically the construction of modern materiality in the Brazilian Social Service, whose genesis derives from conservative thinking and attempts to break from this conservatism to the crisis of materiality of the profession through the invocation of neoconservatism, derived from postmodern influxes. Therefore, the research studies focus on the production of Social Service knowledge through Master's Dissertations, referenced in Marxist critical social theory based on the dialectical historical method. In methodological terms, it is typified as a bibliographic research with the adoption of the state of the art of Master's Dissertations of the Post-Graduation Program in Social Service of the Federal University of Paraíba from the authors, thematic indicators and areas of knowledge. As an investigative cut, the Dissertations defended in the area of Theoretical-practical Rationale were followed to establish a second cut, of a temporal nature, between the years 2007 to 2017 and, finally, it was decided to analyze the Dissertations, whose object of analysis was the Professional Practice. For the analysis of the productions through the State of the Art we used methodologies of a qualitative and quantitative nature. The relevance of the research referred to herein lies in the attempt to deepen the debate and contribute to the production of knowledge in the area of Brazilian Social Service about the crisis of its critical materiality to the postmodern influxes in production, serving with analytical material for reflection on the own profession and its tendencies. Conclusively, the results of the analyzes of the Dissertations on the professional practice of the social worker presented in their empirical contents a tendency to neoconservative practices in the postmodern profession. This is a concern for the profession, but in the productions of the Dissertations, no elements were identified that identified a postmodern tendency around the thematic, author and knowledge area indicators. Thus, the investigative findings affirm the hypothesis of the research that although hegemonic remains the production of the knowledge in the Social Service, based on the critical Marxist materiality, emerges neoconservative inflows, derived from postmodernity. Faced with this affirmation, it is necessary to reflect that strategies must be built to confront the emerging neoconservative tendency that puts at risk the ethical-political project of the profession and the values and principles that underpin it.